NKG2A Expression Is Not per se Detrimental for the Anti-Multiple Myeloma Activity of Activated Natural Killer Cells in an In Vitro System Mimicking the Tumor Microenvironment - Mahaweni, Niken M.; Ehlers, Femke A. I.; Sarkar, Subhashis; Janssen, Johanna W. H.; Tilanus, Marcel G. J.; Bos, Gerard M. J.; Wieten, Lotte (Frontiers in Immunology, 2018)
Natural Killer (NK) cell-based immunotherapy is a promising therapy for cancer patients. Inhibitory killer immunoglobulin-like receptors (KIRs) and NKG2A are required for NK cell licensing but can also inhibit NK cell effector function. Upon reconstitution in a stem cell transplantation setting or after ex vivo NK expansion with IL-2, NKG2A is expressed on a large percentage of NK cells. Since the functional consequences of NKG2A co-expression for activated NK cells are not well known, we compared NKG2A+ vs NKG2A- NK cell subsets in response to K562 cells, multiple myeloma (MM) cell lines and primary MM cells. NK cells were isolated from healthy donors (HLA-C1+C2+Bw4+) and activated overnight with 1000U/ml IL-2. NK cell degranulation in subsets expressing KIRs and/or NKG2A was assessed at 21 or 0.6% O2. Activated NKG2A+ NK cell subsets degranulated more vigorously than NKG2A- subsets both at 21 and 0.6% O2. This was irrespective of the presence of KIR and occurred in response to HLA deficient K562 cells as well as HLA competent, lowly expressing HLA-E MM cell lines. In response to primary MM cells, no inhibitory effects of NKG2A were observed, and NKG2A blockade did not enhance degranulation of NKG2A+ subsets. KIR- NK cells expressing NKG2A degranulated less than their NKG2A- counterparts in response to MM cells having high levels of peptide-induced membrane HLA-E, suggesting that high surface HLA-E levels are required for NKG2A to inhibit activated NK cells. Addition of daratumumab, an anti-CD38 to trigger antibody-dependent cellular cytotoxicity (ADCC), improved the anti-MM response for all subsets and degranulation of the KIR-NKG2A- “unlicensed” subset was comparable to KIR+ or NKG2A+ licensed subsets. This demonstrates that with potent activation, all subsets can contribute to tumor clearance. Additionally, subsets expressing KIRs mismatched with the HLA ligands on the target cell had the highest level of activation in response to MM cell lines as well as against primary MM. Our current study demonstrated that if NK cells are sufficiently activated, e.g. via cytokine or antibody activation, the (co-) expression of NKG2A receptor may not necessarily be a disadvantage in an NK cell-based therapy.